Clipping aneurysms via a fully endoscopic transcranial approach - Zhengxing Xie; Yan Zhuang; Jieping Liu (Scientific Reports)
Abstract Here we presented the initial experience of clipping aneurysms using fully endoscopic techniques and aimed to evaluate the safety and feasibility of fully endoscopic techniques for aneurysms. This was a retrospective single-center study in which patients were scheduled to undergo aneurysm clipping using fully endoscopic techniques. We collected patients’ records, radiological neuroimaging, aneurysm-related variables and surgical procedures in detail, as well as postoperative outcomes. All patients were followed up for neurological examinations and computed tomography (CT) as well as computed tomography angiography (CTA) regularly after surgery. We reviewed the radiological and clinical data of 7patients who underwent aneurysm clipping via fully endoscopic techniques at our department from Jan. 2022 to Jul. 2024, including 2 middle cerebral artery aneurysms, 3 cerebral anterior communicating artery aneurysms, 1 anterior cerebral aneurysm and 1 ophthalmic aneurysm. No uncontrolled rupture of aneurysm occurred during operation. Postclipping endoscopic inspection as well as postoperative CTA demonstrated complete occlusion of the aneurysm and preservation of parent, branching, and perforating vessels. None postclipping cerebral infarction caused by branch or perforator compromise were observed after clipping. No mortality was recorded. Follow-up ranged from 1 to 10 months. Six patients (71.4%) showed excellent or good recoveries. The remaining patient recorded improved KPS. With the accumulation of experience and technological progress, the fully endoscopic technique could enable safe and effective clipping of an aneurysm, which provided valuable information for decision-making during surgery and shed a new light on aneurysms clipping.